2018
DOI: 10.1107/s2052252518003573
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide hydrolysis as a model system for understanding flux through a branched reaction scheme

Abstract: Kinetic rates and computer simulations can explain regioselectivity and stereoconfiguration in the products of enzyme-catalyzed epoxide hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The case of StEH1 thus highlights the importance of considering the energies of all steps of the reaction mechanism in order to reproduce and understand the origins of the selectivity. It should be mentioned that other computational techniques, such as EVB, QM/MM, and MD simulations, have also been used to study the mechanism and selectivity of different soluble epoxide hydrolases. ,, …”
Section: Soluble Epoxide Hydrolasementioning
confidence: 99%
“…The case of StEH1 thus highlights the importance of considering the energies of all steps of the reaction mechanism in order to reproduce and understand the origins of the selectivity. It should be mentioned that other computational techniques, such as EVB, QM/MM, and MD simulations, have also been used to study the mechanism and selectivity of different soluble epoxide hydrolases. ,, …”
Section: Soluble Epoxide Hydrolasementioning
confidence: 99%
“…An epoxide hydrolase from Solanum tuberosum (StEH1) is a well-studied enzyme with a buried active site and a well-defined main tunnel providing access into the catalytic triad. As an attractive target for protein engineering, it has been intensively studied using both experimental [16,17,18,19,20,21,22,23] and computational methods [18,20,23,24,25,26,27]. Solanum tuberosum epoxide hydrolase belongs to the α/β-hydrolase family.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, plant EHs are usually highly regio- and/or stereoselective [ [22] , [66] , [67] , [68] ] towards specific substrates. This issue was carefully analyzed both experimentally and theoretically in StEH1, VrEH2 and Phaseolus vulgaris PvEH3 [ [23] , [69] , [70] , [71] , [72] , [73] ]. Reports have shown that modification of the stereo- and regioselectivity of the enzymes is related to the direction of the attack of water molecules and stabilization of particular transition states [ 72 ].…”
Section: Discussionmentioning
confidence: 99%